Financing and professional training: Analysis of existing resources for the development of micro and small enterprises (MSEs) in Amazonas (Research, Society and Development, 2023)
This article aims to identify the main sources and support actions provided by the State of Amazonas for the development of micro and small businesses in the region. The importance of this research is due to the fact that micro and small companies (MSE) are of great importance in any economy in the world, either due to their enormous capacity to generate jobs, or due to the endless number of establishments distributed geographically, making it possible to meet individual or collective needs. The research is qualitative and descriptive research. It was developed through a documentary survey on websites of public financial institutions and private companies, which help in the development of micro and small companies. In the results found, it is possible to identify six institutions that help in the development of micro and small companies in Amazonas; Among them, two are financing and four that improve professional training.